Strategi Branding Dan Digital Marketing Pada UMKM Untuk Membangun Identitas Brand Di Desa Nglebak (Jurnal Manajemen Kreatif dan Inovasi, 2023)
The development of the times and technology demands that many people be able to balance in the realm of work, such as UMKM. In its development, it is required to introduce and market its products more easily and modernly. This is what gave rise to the term "Digital Marketing", product marketing that utilizes the internet and other interactive technologies to connect dialogue between producers and consumers. The writer who does community service in Nglebak Village, Bareng District, Jombang Regency helps several UMKM in introducing what Digital Marketing is and how to get started. With the method of implementing UMKM socialization which invites a resource person in his field. Followed by assistance in creating brand identity and E-Commerce. It ends with the physical delivery of brand identity such as business cards, business stickers, etc to UMKM. It was concluded that UMKM in Nglebak Village, who previously did not know the importance of brand identity and Digital Marketing, can now understand the importance of a brand identity and Digital Marketing after following the stages of the community service implementation method carried out by the author.